Thiotepa-based high-dose therapy for autologous stem cell transplantation in lymphoma: a retrospective study from the EBMT - Sellner, Leopold; Dreger, Peter (Bone marrow transplantation, 2016)
Clinical information about thiotepa-based autologous stem cell transplantation (auto-SCT) outside the primary central nervous system lymphoma (PCNSL) field is sparse. In this registry-based retrospective study, we evaluated potential risks and benefits of thiotepa-based preparative regimens compared with BEAM (carmustine, etoposide, cytarabine, melphalan) in auto-SCT for diffuse large B-cell lymphoma (DLBCL, excluding PCNSL), follicular lymphoma (FL) or Hodgkin lymphoma (HL). A total of 14 544 patients (589 thiotepa and 13 955 BEAM) met the eligibility criteria, and 535 thiotepa- and 1031 BEAM-treated patients were matched in a 1:2 ratio for final comparison. No significant differences between thiotepa and BEAM groups for any survival end point were identified in the whole sample or disease entity subsets. For a more detailed analysis, 47 TEAM (thiotepa, etoposide, cytarabine, melphalan)-treated patients were compared with 75 matched BEAM patients with additional collection of toxicity data. Again, there were no significant differences between the two groups for any survival end point. In addition, the frequency of common infectious and non-infectious complications including secondary malignancies was comparable between TEAM and BEAM. These results indicate that thiotepa-based high-dose therapy might be a valuable alternative to BEAM in DLBCL, HL and FL. Further evaluation by prospective clinical trials is warranted.
Published 16 November 2015
Gesehen am 05.05.2020